Tingkat Kepentingan Serta Kinerja Atribut Produk Dan Pelayanan Di Rumah Makan Bebek Gendut, Bubulak, Kota Bogor - Mahendraswari, Rekha; Nurmalina, Rita (Jurnal Aplikasi Manajemen, 2013)
RM Bebek Gendut is a special traditional restaurant that serves duck cookery. The intention of this research are to describe about characteristics of customer, to analyse the process of customer desicion making, and also to analyse the importance and performance of product and service atrribute. In majority, customers in RM Bebek Gendut are coming from Bogor City, women, about 21 to 30 years old, haven’t married yet, their final formal education are at senior high school, work as college student, and their own monthly earning are about Rp 1.000.000 to Rp 1.999.999. Based on the result of Customer Satisfaction Index (CSI) calculation, the customer satisfaction index is 75,05% which categorized as satisfied. Based on the result of Importance and Performance Analysis (IPA), there is an attribute that have to be focused and repaired that is waitress hospitality and courtesy.